Ferroelectric Photocurrent Effect in Polycrystalline Lead‐Free (K0.5Na0.5)(Mn0.005Nb0.995)O3 Thin Film. Issue 1 (13th September 2012) - Park, Jungmin; Won, Sung Sik; Ahn, Chang Won; Kim, Ill Won; Brennecka, G. L.
<x xml:space="preserve">Abstract</x> We deposited (K0.5Na0.5)(Mn0.005Nb0.995)O3 (KNMN) thin films on Pt(111)/TiO2/SiO2/Si(100) substrates with a top electrode of indium tin oxide and investigated photocurrent properties in the wavelength range of 300−400 nm. Before the photocurrent measurement, the KNMN film was poled by applying a DC voltage. The photocurrents strongly depend on the wavelength of the incident photon energy. The photocurrents of the first measurement with poling in the up (−5 V) and down (+5 V) states were 21 and 3.2 nA/cm2, respectively, at 344 nm. The difference in the photocurrents in both poling directions was explained by a space charge due to an asymmetric Schottky barrier height, which was caused by an internal electric field and polarization in the KNMN thin film.